2016
DOI: 10.1038/srep21959
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Identification of Liver Cancer Microfoci Using a Targeted Near-Infrared Fluorescent Probe for Imaging-Guided Surgery

Abstract: Difficulties in the highly sensitive detection of tumour microfoci represent a critical obstacle toward improved surgical intervention in liver cancer. Conventional preoperative imaging methods and surgeons’ subjective experience are limited by their inability to effectively detect tumour lesions measuring less than 2 mm; however, intraoperative fluorescence molecular imaging may overcome this limitation. Here, we synthesised an arginine-glycine-aspartic acid (RGD)-conjugated mesoporous silica nanoparticle (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 47 publications
1
58
1
Order By: Relevance
“…Fluorescent labeling (FITC) and fluorescent microscope were used to investigate the ability of free peptide connecting to the same receptor (Oyama et al, 2003). Cyclic-RGD which binds specifically to liver cancer, was another probe employed by Zeng et al in 2016 to provide a detection system for liver cancer cells using mesoporous silica nanoparticle (MSN) along with indocyanine green (ICG) dye. As this system applied a fluorescent probe combining with intraoperative optical imaging, the surgical outcomes can improve significantly .…”
Section: Identification and Visualization Of The Molecules And Metabomentioning
confidence: 99%
“…Fluorescent labeling (FITC) and fluorescent microscope were used to investigate the ability of free peptide connecting to the same receptor (Oyama et al, 2003). Cyclic-RGD which binds specifically to liver cancer, was another probe employed by Zeng et al in 2016 to provide a detection system for liver cancer cells using mesoporous silica nanoparticle (MSN) along with indocyanine green (ICG) dye. As this system applied a fluorescent probe combining with intraoperative optical imaging, the surgical outcomes can improve significantly .…”
Section: Identification and Visualization Of The Molecules And Metabomentioning
confidence: 99%
“…However, due to the high molecular weight and long circulation time in vivo, the detection of HCC with GPC3 antibody probes is slow. Phage display technology, a highly efficient tool to identify small peptides with affinity to a target, has been investigated in recent years for use in the clinical diagnosis and treatment of various types of cancers . Hence, the discovery of peptides functionally targeting HCC cells has received great attention as a target of imaging diagnostic methods and to be applied as a potent target therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A group synthesized arginine–glycine–aspartic acid (RGD)-conjugated ICG mesoporous silica nanoparticles as an intraoperative fluorescent probe and used the probe to test selectivity. 92 The results showed that this novel probe led a significantly enhanced optical signal in hepatic tumor lesions, provided remarkable optical contrast at the liver tumor margin, and displayed a high potential for the detection of residual microtumors.…”
Section: Clinical Applications Of Fgs For Tumorsmentioning
confidence: 92%